Interwencje walutowe jako element polityki banków centralnych - Pszczółka, Ireneusz (Gospodarka w Praktyce i Teorii, 2012)
This paper discusses the issue of central banks intervene in foreign exchange markets in order to achieve a variety of overall economic targets. The main immediate objectives of this intervention are: to influence the level of the exchange rate; to dampen exchange rate volatility or supply liquidity to foreign exchange markets; and to influence the amount of foreign reserves. This paper focuses also on different channels of influence. The main stress was put on the analyses of the effectiveness of some examples of foreign exchange intervention conducted by some central banks, both form emerging and developed economies.